Application of e-learning in teaching elementary statistics course - Aziz, Fakhrul Anuar; Saleh, Abdul Razak; Othman, Abu Talib (2000)
In this study, the authors evaluated how lecture-based education could best be supplemented with online learning strategies.More than 4000 new students in Universiti Utara Malaysia (UUM) register for Elementary Statistics course every year.The number of student per class is about 100. Furthermore; the university is lack of the academic staff. The students did not perform very well in this course because due to very weak background in mathematics.With the use of recent technology, learning materials can be kept in the server where it can stimulate the students to keep revising the lesson repeatedly.Now UUM is exploring this learning concept.